Sustainable planning of cross-border cooperation: a strategy for alliances in border cities - Kurowska-Pysz, Joanna (2018)
In recent years, cooperation among nations has become a critical issue towards sustainable development of neighbor cities in border areas. In this regard, sustainable common planning approaches and policies are an increasing reality, particularly in European territories. Considering the significant amount of cross-border cooperation (CBC) projects and strategies within Europe, it is crucial to promote research approaches that are able to identify the most positive approaches towards the establishment of alliances in border territories, serving as pivotal methodologies for achieving success. Contextually, the present study considered direct and indirect research methods and tools, literature reviews, data collection, computer-assisted telephone interviewing (CATI) and computer-assisted web interview (CAWI), all applied over two European border cities: Cieszyn (Poland) and Cesky Tesin (Czech Republic). These methods enabled the assembly of perspectives of local authorities, public and private institutions, non-governmental organizations, and entrepreneurs from the cities under study. Through the analysis of the collected data, five conditions have been identified for the success of strategic alliances in CBC projects: (i) well defining the alliance goals; (ii) ensuring participation in the alliance of various groups of stakeholders; (iii) involvement of both partners with extensive experience in CBC; (iv) ensuring the coherence of the key objective; and (v) guaranteeing the alliance benefits both sides. These conditions might effectively contribute to achieve more successful outputs in CBC projects, highlighting the relevance of previously developed strategies on the definition of future approaches.